Overexpression of an Antisense RNA of Maize Receptor-Like Kinase Gene ZmRLK7 Enlarges the Organ and Seed Size of Transgenic Arabidopsis Plants - He, Chunmei; Wang, Juan; Dong, Rui; Guan, Haiying; Liu, Tieshan; Liu, Chunxiao; Liu, Qiang; Wang, Liming (Frontiers in Plant Science, 2020)
Leucine-rich repeat (LRR)-receptor-like protein kinases (LRR-RLKs) play vital roles in plant growth, development, and responses to environmental stresses. In this study, a new LRR-RLK gene ZmRLK7 was isolated from maize and its function on plant development was investigated through ectopic expression in Arabidopsis. The spatial expression pattern analysis reveals that ZmRLK7 is highly expressed in in embryos right prior to programmed cell death (PCD) of starchy endosperm tissues and its encoded protein was localized to both plasm and nuclear membranes subcellularly. Overexpression of sense ZmRLK7 reduced the plant height, organ size such as petal, silique, seeds, and 1000-seed weight in transgenic lines, while the antisense transgene enlarged these traits. Cytological analysis suggested that ZmRLK7 negatively regulates petal size through restricting both cell expansion and proliferation. In addition, abnormal epidermal cell structure was observed, and the stomata number decreased obviously in sense ZmRLK7 transgenic lines with a lower stomatal index than that in wild type. Quantitative RT-PCR analysis indicated that transcript levels of genes that involved in brassinosteroid and ERACTA signaling pathway were coordinately altered, which could partially explain the phenotypic variation. Moreover, overexpression of antisense ZmRLK7 substantially rescued the Arabidopsis bak1-3 mutant phenotype. All these results together suggest that ZmRLK7 can serve as an important regulator in regulating plant architecture and organ size formation. This work will provide insights into understanding the function of ZmRLK7 in maize.